Clinical Application Evaluation of Elecsys® HIV Duo Assay in Southwest China - Yang, Mei; Yang, Wenjuan; Shi, Wu; Tao, Chuanmin (Frontiers in Cellular and Infection Microbiology, 2022)
Background HIV/AIDS continues to be a serious health concern of morbidity and mortality globally, and novel HIV testing is still an important component of diagnosing HIV earlier and reducing the spread of HIV. The Elecsys® HIV Duo assay is a 4th generation assay that can detect both HIV-1 p24 antigen (Ag) and HIV-1/2 antibody (Ab) in parallel and show the subresults for the Ab and Ab units. Objectives To evaluate the clinical performance of the Elecsys® HIV Duo assay on the new cobas E 801 analyzer using a large number of clinical samples from a population in southwest China. Methods We collected testing results and information from all patients in a large general hospital. All eligible clinical specimens were first analyzed using the Elecsys® HIV Duo assay. The test results are given either as reactive or nonreactive as well as in the form of a cutoff index (COI). All initially reactive specimens were retested in duplicate with a 3rd-generation kit. Supplementary tests were divided into Ab confirmation tests and HIV-1 nucleic acid tests. GraphPad Prism and Python were used for plotting, and SPSS 21.0 software was used for statistical analysis. Results A total of 186391 specimens were received, and 436 patients were confirmed to be positive for HIV. Among the 86 cases with contact history available, there were more males than females, and heterosexual transmission was the most common route of HIV infection. The Elecsys® HIV Duo assay displayed 99.94%, 99.93% and 99.98% specificity for inpatient, outpatient and physical examination patients, respectively. The median COI ratios of the false-positive group were significantly lower than those of the true-positive group. Conclusions The Elecsys® HIV Duo test (Cobase801 analyzer) differentiates the detection of HIV-1 p24 Ag and HIV-1/2 Ab with high specificity and facilitates the diagnosis of patients with early HIV infection. Therefore, the Elecsys®HIV Duo test is used for differentiation of antigen and antibody reactivity, making it suitable for routine clinical diagnosis.